Cyber-activism on the dissemination of #Gejayanmemanggil: Yogyakarta’s student movement - Nofrima, Sanny; Nurmandi, Achmad; Kusuma Dewi, Dian; Salahudin, Salahudin (Faculty of Communications Science, Dr. Soetomo University, 2020)
The use of social media on Twitter can generate new movements to improve the welfare of the community, one of which #Gejayanmemanggil in forming a new campaign to move a united mass. The research used Nvivo12 Plus-based technology applications to obtain Eisen data. This study revealed the use of social media Twitter on the dissemination of #Gejayanmemanggil information. The qualitative method was employed to find a model for social media use as mass communication. The data in this study was taken from Twitter. Results of the data analysis showed that #Gejayanmemanggil proved to be very effective activity on student social movement.